2012
DOI: 10.4236/fns.2012.310188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biscuit Baking Conditions on the Stability of Microencapsulated 5-Methyltetrahydrofolic Acid and Their Physical Properties

Abstract: Among the folate compounds, 5-methyltetrahydrofolic acid (5-CH 3 THF) is regarded as one of the most bioactive forms of folate. It is regarded as the better source of folate to humans as compared to folic acid, a synthetic form of folate, which is used for fortifying foods to prevent the incidence of neural tube defects in the new born babies. The use of 5-CH 3 THF as an alternative fortificant, in place of folic acid, has been explored by various researchers. However, fortification of 5-CH 3 THF is problemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…baking temperature as compared to chicken biscuits baked at a lower temperature. Shrestha et al (2012) also observed increased hardness and breaking time of 5-methyltetrahydro folic acid microencapsulated biscuits baked at Ͼ200°C than biscuits baked at 170-180°C for longer time due to carbonization and entrapment of moisture in matrix. They also suggested that with an increase in time and temperature, further development of gluten matrix as well as starch gelatinization and retrogradation occurred, which hampered the release of moisture due to sealing of crust and plasticization of proteins and starch.…”
Section: Development Of Nutritional Carabeef Cookiesmentioning
confidence: 75%
See 1 more Smart Citation
“…baking temperature as compared to chicken biscuits baked at a lower temperature. Shrestha et al (2012) also observed increased hardness and breaking time of 5-methyltetrahydro folic acid microencapsulated biscuits baked at Ͼ200°C than biscuits baked at 170-180°C for longer time due to carbonization and entrapment of moisture in matrix. They also suggested that with an increase in time and temperature, further development of gluten matrix as well as starch gelatinization and retrogradation occurred, which hampered the release of moisture due to sealing of crust and plasticization of proteins and starch.…”
Section: Development Of Nutritional Carabeef Cookiesmentioning
confidence: 75%
“…This is in agreement with Lara et al (2011) that showed an increase in oven temperature decreases the lightness of biscuit, independent of heat transfer mode of the oven temperature to the product (Ͼ190°C). Shrestha et al (2012) also observed golden brown color of optimally baked biscuits at 180°C, but at a higher temperature (200-220°C), the golden brown color of biscuits turned to intense red and dark resulting into higher redness and hue angle values.…”
Section: Development Of Nutritional Carabeef Cookiesmentioning
confidence: 76%
“…Moisture content of corn starch added biscuits was more (5.3%) compared to wheat flour added biscuits. Low moisture content in biscuits could result in brittleness (Shrestha, Arcot, Dhital, & Crennan, 2012). It has been widely reported that nonuniform distribution of moisture in the biscuit during baking and drying affect the texture formation and hardness (Ahmed & Hussein, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The weight of the corn biscuits was found to be higher than the wheat flour added biscuits. This may have slight bearing on the quality of biscuits as the low density gives more volume and a lighter bite (Davidson, 2017). The spread ratio of corn biscuit and wheat flour added biscuit was found to be 3.28 g/mm and 3.13 g/mm, respectively (Table 5).…”
Section: Physical Properties Of Biscuitsmentioning
confidence: 99%
“…The retention of folic acid content in the biscuits fortified with the encapsulated 5-CH3THF was high (19.1 ± 3.0, 8.5 ± 1.1, 4.9 ± 0.5 at 180, 200, and 220°C, respectively) compared to that in the biscuits fortified with the unencapsulated 5-CH3THF (5. 4 ± 0.4, 6.7 ± 1.0, 4.4 ± 0.6 at 180, 200, and 220°C, respectively) (Shrestha et al 2012). Tomiuk et al (2012) prepared l-5-methyltetrahydrofolic acid (L-5-MTHF) microcapsules using skim milk as the encapsulating agent for the fortification of bread to increase its bioavailability.…”
Section: Micronutrients Fortification: Unencapsulated Vs Microencapsmentioning
confidence: 99%